Irbesartan desmotropes: Solid-state characterization, thermodynamic study and dissolution properties - Andrea Mariela Araya-Sibaja; Carlos Eduardo Maduro de Campos; Cinira Fandaruff; José Roberto Vega-Baudrit; Teodolito Guillén-Girón; Mirtha Navarro-Hoyos; Silvia Lucía Cuffini (Elsevier, 2019)
Irbesartan (IBS) is a tetrazole derivative and antihypertensive drug that has two interconvertible structures, 1H- and 2H-tautomers. The difference between them lies in the protonation of the tetrazole ring. In the solid-state, both tautomers can be isolated as crystal forms A (1H-tautomer) and B (2H-tautomer). Studies have reported that IBS is a polymorphic system and its forms A and B are related monotropically. These reports indicate form B as the most stable and less soluble form. Therefore, the goal of this contribution is to demonstrate through a complete solid-state characterization, thermodynamic study and dissolution properties that the IBS forms are desmotropes that are not related monotropically. However, the intention is also to call attention to the importance of conducting strict chemical and in solid-state quality controls on the IBS raw materials. Hence, powder X-ray diffraction (PXRD) and Raman spectroscopy (RS) at ambient and non-ambient conditions, differential scanning calorimetry (DSC), hot stage microscopy (HSM), Fourier transform infrared (FT-IR) and scanning electron microscopy (SEM) techniques were applied. Furthermore, intrinsic dissolution rate (IDR) and structural stability studies at 98% relative humidity (RH), 25 °C and 40 °C were conducted as well. The results show that in fact, form A is approximately four-fold more soluble than form B. In addition, both IBS forms are stable at ambient conditions. Nevertheless, structural and/or chemical instability was observed in form B at 40 °C and 98% RH. IBS has been confirmed as a desmotropic system rather than a polymorphic one. Consequently, forms A and B are not related monotropically. Keywords: Irbesartan, Solid-state characterization, Intrinsic dissolution rate, Tautomerism, Desmotropic forms